Traditional uses, phytochemistry, pharmacology, toxicology, and quality control of Rhododendron dauricum L. leaves: A comprehensive review. (6th April 2023) - Liang, Qian; Hu, Jia-Xin; Zhang, Xin-Min; Xu, Wen-Hui
Abstract: Ethnopharmacological relevance: Rhododendron dauricum L. is a traditional herb mainly distributed in the northeast China, Mongolia, Korea Peninsula, and Russia Far East. The dried leaves of Rhododendron dauricum L. (LRD), generally known "Man Shan Hong" have been traditionally applied as folk medicines to treat fever, copious phlegm, asthma, acute and chronic bronchitis, sore throat, dysentery, diabetes mellitus, cancer, and hypertension. To date, no comprehensive review on R. dauricum leaves has been published. Aim of the study: Recent progresses in traditional use, phytochemistry, pharmacology, toxicology, and quality control of R. dauricum leaves are systematically presented and critically evaluated in order to provide scientifical basis for its reasonable utilization and further study. Materials and methods: All information about R . dauricum leaves were retrieved from internet scientific databases including Sci-Finder, Web of Science, PubMed, CNKI, Google Scholar, Elsevier, Wiley, ACS publications, SpringerLink, and the Chinese Pharmacopoeia between 1970 and 2022. Plant names were validated by "The Plant List" (http://www.theplantlist.org/ ). Results: So far, 114 structurally diverse compounds have been isolated and identified from LRD, mainly including flavonoids, diterpenoids, triterpenoids, meroterpenoids, phenols, and 54 volatile components were identified from the essential oils of LRD. Among these, flavonoids are considered as characteristic components and major bioactive phytochemicals. The crude extracts and compounds from LRD have been reported to possess broad pharmacological effects including antitussive and expectorant, anti-inflammatory, anti-HIV, antibacterial, and cytotoxic effects, etc. Conclusions: As a traditional herb medicine, LRD have been used popularly. On the one hand, traditional uses of LRD provide valuable directions for current research; on the other hand, modern phytochemical and pharmacological studies verify the traditional uses to make its reasonable utilization. However, several defects such as active components determination, in vivo and clinical pharmacological evaluation, toxicology assessment, and quality control of LRD need further study. Graphical abstract: Image 1 Highlights: A review to summarize the traditional uses, phytochemistry, pharmacology, toxicology, quality control of Rhododendron dauricum leaves. So far, 114 diverse compounds have been isolated and 54 volatile components were identified from LRD. The chemical components showed antitussive and expectorant, anti-inflammatory, effects, etc. The links between traditional uses, phytochemistry, pharmacology, toxicity and quality control have been discussed.